Implementing resource efficient and cleaner production as a tool to reduce carbon tax in the manufacturing industries - Mashau, Phathutshedzo Ndifelani Maggie (My University, 2022)
The carbon tax came into effect in South Africa in June 2019 to reduce greenhouse gas emissions (GHGs). With its first phase focusing on scope one carbon emissions, facilities that combust 10 megawatts or more became liable for a carbon tax. Among these are large emitting industries like manufacturing plants. This has placed a greater burden on industries under the current economic status, worsened by the COVID-19 pandemic. In addition to paying for the scope one tax liabilities, companies must report verified carbon emission and energy consumption patterns (energy plans), which require resources. Implementing resource-efficient and cleaner production (RECP) methodologies in industries have been the mandate of the National Cleaner Production Centre South Africa (NCPCSA), the programme of the national government, to reduce the environmental footprint and improve industry competitiveness. As a result, many industries in South Africa are focused on reducing their resource consumption and environmental footprint by improving efficiencies in production processes. This research evaluated the benefit of the implementation of RECP as a tool to reduce carbon tax in manufacturing industries. Quantitative methods were applied in the data collection and analysis of three manufacturing plants that embarked on RECP implementation. Semistructured interviews were also conducted with expert consultants and company managers who were part of the team for the RECP implementation facilitated by the NCPCSA. Quantitative data were collected during the RECP assessment and the case study phase of RECP implementation. Regression analyses were applied to determine the energy baseline for each plant for further evaluation of the RECP implementation results. The quantitative results of the RECP implementation have shown a reduction in energy consumption, equivalent carbon emissions, and associated costs including equivalent carbon tax savings in all three plants. The interview responses have shown that the perception of RECP expert consultants and company managers support that implementation of the RECP methodologies in industries provides the basis for measurement and verification of energy consumption and equivalent greenhouse gas emissions for reporting purposes as per legislative requirements. They also agreed that RECP is beneficial in reducing energy consumption, greenhouse gas emissions, and associated costs (resource costs and carbon tax). These reductions in GHG emissions and costs can reduce the manufacturing plants’ carbon tax liabilities if the reduced carbon emissions fall under scope one in the current phase of carbon tax implementation (June 2019- December 2022). Nevertheless, the resulting reduction in energy consumption and equivalent carbon emissions were sufficient to draw some conclusions and recommendations.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Carbon tax; Greenhouse gas emissions (GHGs); Resource-efficient and cleaner production